2009
DOI: 10.1007/s11032-009-9343-2
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput SNP genotyping with the GoldenGate assay in maize

Abstract: Single nucleotide polymorphisms (SNPs) are abundant and evenly distributed throughout the genomes of most plant species. They have become an ideal marker system for genetic research in many crops. Several high throughput platforms have been developed that allow rapid and simultaneous genotyping of up to a million SNP markers. In this study, a custom GoldenGate assay containing 1,536 SNPs was developed based on public SNP information for maize and used to genotype two recombinant inbred line (RIL) populations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
183
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(203 citation statements)
references
References 21 publications
(31 reference statements)
14
183
2
1
Order By: Relevance
“…The Illumina GoldenGate BeadArray is a medium-density genotyping platform that can interrogate up to 1,536 SNPs per array. The GoldenGate technology is now being used for genetic analysis in several crop species including barley (Rostoks et al 2006), soybean (Hyten et al 2008), and maize (Yan et al 2009;Yan et al 2010) where the rates of successful scoring of SNP data were ≥90 % (Hyten et al 2008;Rostoks et al 2006;Yan et al 2010). We found 1,064 of 1,536 tested SNPs (69 %) to be scoreable and mappable in at least one of two C. mollissima mapping families.…”
Section: Marker Identification and Characterizationmentioning
confidence: 87%
See 1 more Smart Citation
“…The Illumina GoldenGate BeadArray is a medium-density genotyping platform that can interrogate up to 1,536 SNPs per array. The GoldenGate technology is now being used for genetic analysis in several crop species including barley (Rostoks et al 2006), soybean (Hyten et al 2008), and maize (Yan et al 2009;Yan et al 2010) where the rates of successful scoring of SNP data were ≥90 % (Hyten et al 2008;Rostoks et al 2006;Yan et al 2010). We found 1,064 of 1,536 tested SNPs (69 %) to be scoreable and mappable in at least one of two C. mollissima mapping families.…”
Section: Marker Identification and Characterizationmentioning
confidence: 87%
“…Although automated clustering using GenomeStudio generally produced one, two, or three distinct clusters corresponding to the expected genotypic classes based on parental genotypes, the data for all SNPs were inspected manually, and genotypic clusters were manually edited when necessary (Yan et al 2010). Genotypes ambiguously located between clusters were scored as missing data.…”
Section: Source Of Estsmentioning
confidence: 99%
“…SNP assay is the test of choice for genomewide genetic analysis, but unfortunately it usually detects only two alleles at each locus (31,32). This biallelic limitation can be overcome by using haplotypes constructed from multiple SNP markers likely to be within the same gene or from SNPs within 10 kb, the average size of LD blocks in maize.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs are generally considered as dispersed markers, even though in some species tend to concentrate more frequently in heterochromatic regions and it is unlikely to cover all the genomic regions assessing just SSRs (Hong et al, 2007;Shirasawa et al, 2010). On the other hand, it has been reported that the validation of SNPs by high-throughput SNP genotyping, like genotyping-bysequencing (GBS), RAD tag sequencing or similar, can be 100-fold faster and 75% less expensive than SSRs detection through an agarose or polyacrylamide gels or capillary sequencing (Jones et al, 2007;Yan et al, 2010). For all these reasons SNPs markers have quickly replaced SSRs in the last few years.…”
Section: Mapping Studies Experimental Populations and Genotyping Mementioning
confidence: 99%